Community renewable energy: What does it do? Walker and Devine-Wright (2008) ten years on. (November 2019) - Creamer, Emily; Taylor Aiken, Gerald; van Veelen, Bregje; Walker, Gordon; Devine-Wright, Patrick
Abstract: In 2008, Walker and Devine-Wright published a short article that is now a key way-marker in the field: 'Community renewable energy: what should it mean?' . A decade on, in this Perspective we revisit Walker and Devine-Wright's paper to re-examine its central themes and to identify opportunities for the coming ten years of community renewable energy (CRE) studies. Our Perspective takes the form of a series of paired reflections from the authors of the original paper and three early career researchers whose work it has influenced. We present these reflections in three themes. First, despite its title, the 2008 article itself is not centrally concerned with meanings, still less what CRE should mean. CRE is always defined by its context, therefore, we argue for an approach that is alive to these contexts. Second, while the article splits 'process' and 'outcome' when conceptualising interpretations of CRE, research labelling elements of CRE as either 'process' or 'outcome' can obscure CRE's complex and entangled dynamics. Third, the past decade of scholarship emerging in this article's wake has tended to concentrate on the means by which CRE develops, rather than on its ends. There is a need for greater attention on the impacts of CRE, particularly its role in achieving just transitions. We propose that new approaches could further galvanise the study of CRE to help better understand what CRE does, for whom and in what contexts.